Helma Berch e o ensino de música no contexto da imigração alemã católica do Vale do Taquari - Ferla, Joselia Jantsch (2009)
The present dissertation, linked to line of research Education and Arts of Postgraduate Program in Education LP4, Federal University of Santa Maria, sought to analyze the trajectory of Helma Bersch teacher, in front of music teaching in the German catholic immigration context, in South of Brazil. This teacher worked professionally in the period of 1932 to 1981, in school society of Dona Rita, located in Arroio do Meio County, in Taquari Valley, northwest region of the state of Rio Grande do Sul. Yet, sought to investigate the process of musical formation of the teacher Helma Berch; to know the musical practices developed in the room of school, as well as to examine the repercussion of Helma s work to the community of Dona Rita. This study, of qualitative nature, utilized the methodological resources of oral history to build the teacher s trajectory, based on Bourdieu (2006), Levi (2006) and Schmidt (2000), in the perspective in which the history of a life is taken as a gateway to the articulation of issues or broader contexts. Also were utilized Kreutz s works (2004, 2000, 1999 and 1994), Garbosa (2006, 2004 and 2003) and Bersch (2006). To analyze the trajectory of the teacher Helma Berch was possible to record the person s history that made of her own life a part of the history of music teaching in the Brazilian schools and bringing to the discussion the specificities in relation to way to conceive the teaching, in period and context analyzed. It was possible to consider about the specificities of pedagogic practices, the didactic materials, the upbringing, the musicals instruments presents in the context, as well as the repercussions of the work developed by Helma in the society of Dona Rita. However, through this study, was possible to highlight the contribution this group of immigrant in the economic and cultural developing this Valley, where the music exerted important function in the integration, identification and diffusion of cultural elements, being the school the place chosen as responsible to reach and to keep the status quo in that time.